Postsynthesis of zwitterionic hydrophilic composites for enhanced enrichment of N‐linked glycopeptides from human serum - Liu, Bin; Wang, Baichun; Yan, Yinghua; Tang, Keqi; Ding, Chuan‐Fan (Rapid communications in mass spectrometry, 2020)
Rationale Glycosylation of proteins plays an important role in life activities, but the concentration of naturally occurring glycopeptides is usually relatively low, and glycosylation has microfacies heterogeneity, so direct mass spectrometry is not feasible. Therefore, selective enrichment of glycopeptides before mass spectrometry has turned into an urgent problem to be resolved. Methods Herein, the zwitterionic L‐cysteine functionalized hydrophilic graphene oxide composite (GO@PDA@MIL‐125‐NH2@Au@L‐Cys) was prepared via a postsynthetic method. The obtained material was used for glycopeptide enrichment. The enriched peptides were then detected using matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOFMS) to demonstrate the enrichment performance of the material. Results In the actual enrichment process, GO@PDA@MIL‐125‐NH2@Au@L‐Cys nanomaterials exhibited high selectivity (1:1000), outstanding sensitivity (0.5 fmol), and excellent repeatability for the enrichment of glycopeptides. In addition, the proposed material showed good performance in the enrichment of glycopeptides from complex biosamples; 56 glycopeptides were detected from 2 μL of human serum using MALDI‐TOFMS. Conclusions The experimental results showed that GO@PDA@MIL‐125‐NH2@Au@L‐Cys exhibited excellent performance on glycopeptide analysis. It has great potential in the enrichment of glycopeptides and provides new ideas for synthetic materials with better enrichment properties in the future.